The Effectiveness Of Talking Chips To Teach Speaking Viewed From Students’ Self-Esteem - Siti Khusnul Faizah (Taqorrub: Jurnal Bimbingan Konseling dan Dakwah, 2020)
This research is aimed at finding out whether: (1) talking chips is more effective than direct instruction to teach speaking; (2) students who have high self-esteem have better speaking skill than those who have low self-esteem; and (3) there is an interaction between teaching methods and students’ self-esteem in teaching speaking. The research method used was an experimental study. The research was conducted at Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ponorogo in the academic year of 2019/2020. The population was the first semester students of Institut Agama Islam Riyadlatul Mujahidin (IAIRM) Ponorogo in the academic year of 2019/2020 which consisted of three faculties. The sample was taken by using cluster random sampling. There were two classes used as samples, namely tarbiyah faculty as the experimental class taught by using talking chips and syariah faculty as the control class taught by using direct instruction. The data of the research were collected using a questionnaire and a speaking test. After the normality and homogeneity tests were conducted, the hypothesis test was done. The data of speaking test were analyzed by using multifactor analysis of variance 2 x 2 and Tukey test. Based on the data analysis, there are some research findings that can be drawn. First, talking chips is more effective than direct instruction to teach speaking. Second, the students who have high self-esteem have better speaking skill than those who have low self-esteem. Third, there is an interaction between teaching methods and students’ self-esteem in teaching speaking.